Maine’s Initiatives in Geriatric Medical Care: Commentary from the Front Lines - Singer, Cliff; Renfrew, Roger (Maine Policy Review, 2015)
Cliff Singer and Roger Renfrew write from their perspectives as medical practitioners and leaders in geriatric medicine to examine issues affecting health care and outcomes for older adults in Maine. Focusing on the acute and primary care systems, they highlight issues and policy recommendations they think are most urgent or helpful.
Keywords: health care; geriatric medicine; Maine